Pesticide residues in food 2004 (Evaluations) : (FAO, 2005)
Published in two volumes, this document contains the summaries of the residue data considered and the recommendations made at the 2004 Joint Meeting of the FAO Panel of Experts on Pesticide Residues in Food and the WHO Core Assessment Group.